Sport Orientation and Athletic Identity of Paralympic Games’ Shooters - Kokaridas ∆ηµήτριος; Natsis Πέτρος; Makropoulos Κωνσταντίνος; Xatzigeorgiadis Αντώνιος; Karpathakis Νικόλαος (Inquiries in Physical Education and Sport, 2005)
The purpose of this study was to examine sport orientation and athletic identity of elite athletes with physical disabilities. Participants were 30 shooting athletes from different national teams of the Paralympic Games 2004. Thirteen (13) participants had acquired disability and seventeen (17) participants had congenital disability. Two athletes had polio syndrome, 12 had spinal cord disability, 9 were amputees and 6 had spina bifida. The training age of the participants ranged from 2 to 28 years. They completed the Sport Orientation Questionnaire (Gill & Deeter, 1988), which assesses scores for the factors of competitiveness, goal orientation and win orientation and the Athletic Orientation Questionnaire (Martin, Adams-Mushett & Smith, 1995) that measures the factors of self-identity, social identity, exclusivity and negative affectivity. The results of the study revealed a satisfactory internal consistency among the factors. In addition, results exposed differences concerning win orientation according to the training age of the participants, along with an effect of the different kinds of disability on self-identity and social identity of the athletes.